Study of Pests and Diseases 10 Accessions of Sowthistle in Organic Cultivation - Tatik Raisawati; Maya Melati; Sandra Arifin Aziz; Mohamad Rafi; Parwito Parwito (University of Prof. Dr. Hazairin, SH, 2022)
Tempuyung (Sonchus arvensis L.) is known in Indonesia as traditional medicine. This study was conducted to observe diseases that attack tempuyung in organic cultivation. Ten accessions of sowthistle were collected from Dramaga, Cibadak, Cicurug, Lembang, Matesih, Sekipan, Tawangmangu, Batu, Banjararum, and Sumbersekar, with altitudes between 186-1280 m above sea level and rainfall of 988-2573 mm. The research was carried out in the organic experimental field of Cikarawang, IPB, Bogor, with a geographical location of 6o30' - 6o45' SL and 106o30'-106o45´ EL and an altitude of 190 m above sea level. The research location is a lowland with 1618 mm of rainfall during the study. Pest identification was carried out in the Plant Clinic laboratory of the Plant Protection Department of IPB. Disease identification was carried out by taking symptomatic plants, then isolated and grown in PDA media and then identified. The results showed that the disease that attacked the sowthistle in this experiment was caused by the bacterium Pseudomonas sp and fungi Fusarium sp. The disease attack rate ranges from 32 to 60%. Disease attacks were controlled by removing the affected plants and then spraying with turmeric solution in a ratio of 1: 10. Pests that attacked sowthistle were snails, grasshoppers, fruit borer caterpillars, and panicle-sucking insects.